Bacteria-mediated precursor-dependent biosynthesis of superparamagnetic iron oxide and iron sulfide nanoparticles - Bharde, Atul A.; Parikh, Rasesh Y.; Baidakova, Marina; Jouen, Samuel; Hannoyer, Beatrice; Enoki, Toshiaki; Bhagavatula L. V. Prasad; Shouche, Yogesh S.; Ogale, Satishchandra B.; Sastry, Murali (Langmuir, 2008)
The bacterium Actinobacter sp. has been shown to be capable of extracellularly synthesizing iron based magnetic nanoparticles, namely maghemite (gamma-Fe2O3) and greigite (Fe3S4) Under ambient conditions depending on the nature of precursors used. More precisely, the bacterium synthesized maghemite when reacted with ferric chloride and iron sulfide when exposed to the aqueous solution of ferric chloride-ferrous sulfate. Challenging the bacterium with different metal ions resulted in induction of different proteins, which bring about the specific biochemical transformations in each case leading to the observed products. Maghemite and iron sulfide nanoparticles show superparamagnetic characteristics as expected. Compared to the earlier reports of magnetite and greigite synthesis by magnetotactic bacteria and iron reducing bacteria, which take place strictly under anaerobic conditions, the present procedure offers significant advancement since the reaction occurs under aerobic condition. Moreover, reaction end products can be tuned by the choice of precursors used.